KEEFEKTIFAN PENDEKATAN KONSTRUKTIVISME TERHADAP KEMAMPUAN PENALARAN MATEMATIS MAHASISWA PADA MATA KULIAH ANALISIS REAL - Fitriani Fitriani; Yulia Anita Siregar (Universitas Islam Sumatera Utara, 2018)
Abstract. This research was conducted at University of Muhammadiyah South Tapanuli in semester VI student of mathematics education program that follow Real Analytical course. This study aims to determine students' mathematical reasoning ability after using constructivism approach and also want to know the effectiveness of constructivism approach to mathematical reasoning ability, as well as expected to give benefit to lecturer of Real Analysis course lecturer. The method used to achieve the goal is by experimental method with pre-experimental design research design. This research produces: A very effective constructivism approach is used to teach real analysis courses. There is an increase in students' mathematical reasoning abilities after using constructivism approach.Keywords: Constructivism, Mathematical Reasoning, Real Analysis.